Analisis Daya Dukung Pondasi Tiang Menggunakan Metode Pile Driving Analyzer (PDA) (Studi Kasus: Jembatan Rengas, Kabupaten Batang Hari) - Raudhati, Emelda (Universitas Batanghari Jambi, 2025)
Foundation as an important element to bear loads and transfer them to the ground. Foundation design considers various aspects, especially soil conditions, to ensure the bearing capacity and stability of the structure. The Pile Driving Analyzer (PDA) method is a testing technique used to assess the bearing capacity of pile foundations through dynamic load analysis. The analysis is performed using the